An Insight into The Perceptions of Biochemistry Teachers Regarding Innovative Teaching Methodologies Employed in Integrated Medical Curriculum - Jan, Fauzia; Aftab, Lubna; Kausar, Uzma; Quresh Hashmi, Ruqayyah; Faisal, Nabeela; Zulfiqar, Saba (Journal of Neonatal Surgery, 2025)
Objective: The objective of the study was to analyze perceptions of medical teachers on newer methodologies used in teaching biochemistry in the integrated medical curriculum Study design: Cross sectional study observational study. Settings: The department of Biochemistry, University Medical & Dental College Faisalabad. Duration: 15th January, 2025 to 15th June, 2025 Methods: The ethical approval was obtained from Ethical review committee of The University of Faisalabad, 52 faculty members from Biochemistry departments of various medical colleges across Pakistan participated in the study. Informed consent was taken; data was collected from participants using a structured questionnaire followed by statistical analysis using IBM SPSS software. Results: Most medical teachers were satisfied with the modern interactive teaching methods. The practice most liked was Case-based learning (44,84.6% teachers), followed by small group discussions (42,80.7%) and then, large group interactive sessions (40,76.9%). However, only 32(61%) teachers supported the flipped classroom method. A statistically significant association was found between teachers’ satisfaction levels and different teaching methodologies when analyzed using the Pearson Chi-square test. Conclusion: Biochemistry teachers accepted the innovative teaching methodologies as these are useful in promoting student centered teaching, engagement and improving the outcomes of teaching in integrated medical curriculum. Broader faculty adoption of these strategies may enhance teaching quality and learning outcomes..